Yellow nail syndrome - A. V. Motorina; T. G. Ruksha (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Yellow nail syndrome is an extremely rare syndrome, mainly in people over 50 years of age, occurring both systemically and in isolation and requiring the most careful collection of anamnesis, since this condition has a close relationship with respiratory diseases, malignant neoplasms of internal organs and rheumatoid arthritis. Moreover, this rare disease is not sufficiently studied to fully understand its pathogenesis and effective treatment. Patients pay attention to the yellow color of the nails, associated with the deposition of melanin, bile pigments and hemosiderin in the submarginal space, slowing down the growth and thickening of the nail. It should be noted that the change in the nail plates can be observed long before the other clinical manifestations of this syndrome are detected, and probably this can in some cases serve as a harbinger of incipient changes in the lung tissue, neoplasms and changes in the lymphatic vessels. In this regard, it is extremely important to clearly differentiate this condition and refer patients to related specialists for verification of the diagnosis and further treatment.